Individual Taxpayer Intentions Towards Spending on Health and Education Tax Relief - Syed Mahathir, Syed Mustaphanin (2023)
In Malaysia, the government introduces different tax policies through the budget presented to the public annually. These policies aim to achieve various targets with the common objective of stimulating the economy and generating higher national income. These policies should influence the spending behavior of taxpayers including their intention to spend on health and education tax relief. Therefore, this study seeks to investigate the intentions of individual taxpayers and the resulting effects on their spending related to health and education tax relief. Data from the Inland Revenue Board and the Department of Statistics show an increase in tax relief offerings, but household expenditure statistics indicate a decline in health and education spending. Researcher discusses the Theory of Planned Behavior (TPB) and the Knowledge-Attitude-Practice (KAP) model as frameworks for understanding behavior and intention. Factors influencing spending intentions, such as attitudes, subjective norms, perceived behavioral control, and tax knowledge, are explored. Questionnaires method is used in with a sample size of 160 respondents within the Klang Valley region. The data analysis process using SPSS software. Reliability analysis indicates high reliability of survey questions. Normality analysis shows data suitability. Factor analysis reveals suitable variables for analysis. Descriptive analysis shows a high level of intention and attitude towards spending on tax relief. The analysis supports the hypotheses and identifies significant positive relationships between attitude, subjective norms, perceived behavioral control, tax knowledge, and intention to spend on health and education tax relief. The results indicate that individuals with more favorable attitudes, who perceive social pressure or influence, have a sense of control, and possess tax knowledge are more likely to have a higher intention to spend on health and education relief. It emphasizes the importance of these factors in shaping intentions and behaviors. The study concludes that attitude, subjective norm, perceived behavioral control, and tax knowledge positively influence intention to spend on health and education tax relief. This research suggests effective communication and awareness campaigns where it emphasizes the significance of these factors in promoting compliance and reducing non-compliance among individual taxpayers.